Strengthening cybersecurity in Singapore : challenges, responses, and the way forward - Luk, Sabrina Ching Yuen (IGI Global, 2020)
This chapter uses a historical perspective to examine the development trajectory of e-government in Singapore, the trends and patterns of cybercrimes and cyber-attacks, and the measures taken by the government to combat cybercrimes and cyber-attacks. It shows that the government has adopted a proactive, holistic, and cooperative approach to cybersecurity in order to tackle the ever-increasing cybersecurity challenges. It has regularly reviewed and improved cybersecurity measures to ensure their effectiveness and strengthened its defense capabilities over time through coordinating national efforts with public and private sectors and cooperating with regional and international counterparts. The chase for a perfect cybersecurity system or strategy is both impossible and unnecessary. However, it is important and necessary to establish a cybersecurity system or formulate a cybersecurity strategy that can monitor, detect, respond to, recover from, and prevent cyber-attacks in a timely manner, and make the nation stronger, safer, and more secure.